The influence of and change in procedural justice on self-rated health trajectories: Swedish Longitudinal Occupational Survey of Health results - Constanze Leineweber; Constanze Eib; Paraskevi Peristera; Claudia Bernhard-Oettel (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVES: Procedural justice perceptions are shown to be associated with minor psychiatric disorders, long sickness absence spells, and poor self-rated health, but previous studies have rarely considered how changes in procedural justice influence changes in health. METHODS: Data from four consecutive biennial waves of the Swedish Longitudinal Survey of Health (SLOSH) (N=5854) were used to examine trajectories of self-rated health. Adjusting for age, sex, socioeconomic position, and marital status, we studied the predictive power of change in procedural justice perceptions using individual growth curve models within a multilevel framework. RESULTS: The results show that self-rated health trajectories slowly decline over time. The rate of change was influenced by age and sex, with older people and women showing a slower rate. After adjusting for age, sex, socioeconomic position, and marital status, procedural justice was significantly associated with self-rated health. Also, improvements in procedural justice were associated with improvements in self-rated health. Additionally, a reverse relationship with and change in self-rated health predicting procedural justice was found. CONCLUSIONS: Our findings support the idea that procedural justice at work is a crucial aspect of the psychosocial work environment and that changes towards more procedural justice could influence self-rated health positively. The reciprocal association of procedural justice and self-rated health warrants further research.